Robot Law: Volume II - Holohan Jr, Martin Michael (My University, 2025)
Robot Law: Volume II (Edward Elgar 2025), edited by Ryan Calo, A. Michael Froomkin and Kristen Thomasen, provides an interdisciplinary examination of contemporary issues in robotics and law, with contributions from a wide array of industry experts and academics. Whereas the first volume of Robot Law grappled with some of the more foundational issues concerning robotics and law, this second volume explores the pressing legal, social and ethical concerns arising from robot systems becoming increasingly embedded within society and being able to (in some respects) operate independently of overt human decision-making. This second volume has four sections which are termed “Beyond neutrality,” “Presentation and manipulation”, “Responsibility and enforcement” and “Individual and relational rights: creativity, expression and privacy.” While these sections tackle different issues pertaining to robotics and law, each section seeks to build upon the previous one by illustrating the interaction between the law and automated systems.
PUBLISHED
Keywords: IT Law and Policy; Legal Reform; law and technology